Persepsi Sakit, Pengetahuan dan Kepuasan dengan Pemanfaatan Pelayanan Kesehatan di Puskesmas - Agustina, Silvia (HIGEIA (Journal of Public Health Research and Development), 2019)
The total of participants beneficiaries National Health Insurance in Puskesmas Kalongan as many as 10.715 people. In 2017 from January to October the total of beneficiaries participants visits decreased with the lowest number of visits by 580 people and the coverage of patient visits was less than target (90 ‰ of 150 ‰). The purpose of this research is to know the correlation between perception about sick, knowledge and satisfaction of beneficiaries of NHI program with health service utilization. This type of research is an analytical survey with cross sectional design. Population and samples from this study were participants of beneficiaries National Health Insurance registered in Puskesmas Kalongan with systematic random sampling technique and determined by using 105 respondents. Instrument used in the research is a questionnaire. Data analysis was done by using Chi-Square test. The result of statistical test showed that there was correlation between perception about sickness (p= 0,007), knowledge (p=0,000) and satisfaction (p=0,024) with utilization of health service at Puskesmas Kalongan, East Ungaran Subdistrict with weak correlation strength (CC= 0,256, CC=0,335, CC=0,258) The research conclude that the perception about sickness, knowledge and satisfaction is related to the utilization of health services in Puskesmas Kalongan. Keywords: Perception about Sickness, Knowledge, Satisfaction, Utilization of Health Service